Imaging large amplitude out-of-plane motion in photoexcited pentafluorobenzene using time-resolved photoelectron spectroscopy: a computational study. Issue 8 (12th July 2018) - Sala, Matthieu; Egorova, Dassia
Abstract : We present simulations of the excited state dynamics and time-resolved photoelectron spectroscopy of photoexcited pentafluorobenzene. Abstract : Excited-state dynamics of pentafluorobenzene is studied in detail for a quartic vibronic coupling model including the six b1 vibrational modes of the molecule and the two lowest excited electronic states. The study analyzes the influence of the large-amplitude out-of-plane vibrational motion on the electronic dynamics and extends to the simulation of the emerging time-resolved photoelectron spectra. The mapping of coherent non-separable electron-nuclear motion into oscillatory photoelectron signals is discussed.